Patrimônio para quem? População negra em situação de rua e as dinâmicas da desigualdade nos espaços patrimonializados em Goyaz - GO - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This study investigates the formation of the first settlements and towns in Brazil, with emphasis on the territorial occupation (invasion) promoted by the Portuguese and on the Eurocentric influence that shaped the architecture and spatial organization of historic cities, such as the former capital of the state of Goiás, the city of Goyaz. The research analyzes the process of patrimonialization of this territory, particularly through the criteria employed by UNESCO for the recognition of its architectural heritage, and how such criteria do or do not engage with the historical and social characteristics of local urban formation. At the same time, the study problematizes the persistence of structural racism as a determining force in the experiences and living conditions of the unhoused Black population within the patrimonialized spaces of the city. It highlights how historical, social, and institutional inequalities continue to marginalize this population, rendering it practically invisible in public policies, heritage discourses, and contemporary urban projects. Through fieldwork, interviews, and bibliographical references, the research proposes a critical reflection on the exclusionary model of heritage management. From this analysis, we emphasize the urgent need for inclusive public policies that acknowledge and act in a humanized manner in favor of unhoused people, particularly those racialized, promoting both their symbolic and concrete inclusion within the patrimonial spaces of the city. As a result of this investigation, we created an affective political fanzine, historically conceived as a form of art and protest. Through it, the presences of unhoused people within Goyaz’s patrimonial spaces are graphically and poetically represented. The fanzine subverts official discourses by reinscribing these lives into the symbolic frameworks of the city, provoking reflection and discomfort, and asserting that heritage also belongs to them. Thus, it becomes an instrument of resistance, denunciation, and reimagination of the patrimonialized urban space.
Heritage for whom? Black homeless population and the dynamics of inequality in heritage spaces in Goyaz - GO
Keywords: Patrimônio; Goyaz; Racismo estrutural; População em situação de rua; Heritage; Goyaz; Structural racism; Unhoused population; CIENCIAS HUMANAS::HISTORIA